Recurrent Acute Myocardial Infarction in Patients with Immune Thrombocytopenic Purpura - Fengyi Shen; Tonga Nfor; Tanvir Bajwa (Journal of Patient-Centered Research and Reviews, 2014)
Immune thrombocytopenic purpura (ITP), also known as idiopathic thrombocytopenic purpura, is an acquired immune-mediated disease of adults and children characterized by a transient or persistent decrease of platelets and, depending upon the degree of thrombocytopenia, an increased risk of bleeding. The use of standard treatments for acute myocardial infarction (AMI), such as antiplatelet agents and anticoagulants, pose serious problems in patients with ITP due to the potential higher risk of bleeding complications. There are no current guidelines available for management of ITP patients with AMI. In this brief review of the limited available literature, we discuss the proposed pathophysiological link between ITP and arterial thrombosis and the challenging medical and interventional treatment of these patients.